Central serous chorioretinopathy following ingestion of sildenafil citrate - Mohammadpour M; Khodaparast M; Khorrami-Nejad M (Clinical Optometry, 2019)
Mehrdad Mohammadpour,1 Mehdi Khodaparast,1 Masoud Khorrami-Nejad1,21Eye Research Center, Farabi Eye Hospital, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Optometry, School of Rehabilitation, Shahid Beheshti University of Medical Sciences, Tehran, IranIntroduction: We report a case of a 35-year-old man who presented with headache followed by decreased vision, metamorphopsia, and altered color perception in his left eye, after repeated intake of sildenafil citrate (four times; 100 mg) in a limited period (3 days).Methods: On the first ocular examination, best-corrected distance visual acuity (CDVA) was 20/80 in his left eye and 20/20 in his right eye. On fundus examination, loss of foveal reflex and serous retinal detachment in the foveal region were detected. Fluorescein angiography of the left eye was compatible with a leakage area with determined borders. The patient was advised to stop sildenafil intake.Results: After 4 weeks, CDVA increased to 20/25, and the fundus examination revealed significant improvement of the macular edema. Optical coherence tomography showed increased foveal thickness to 350 μm.Conclusion: Advising patients with central serous chorioretinopathy to stop sildenafil intake should be considered.Keywords: central serous chorioretinopathy, sildenafil citrate, serous retinal detachment